A Walk Along the River Betwa. (May 2023) - Singh, Radhika; Joshi, Shail
The Bundelkhand region has long been in the news for its lack of development, political tussles and water insecurity. By embarking on a riverwalk in Bundelkhand, where we followed the Betwa River on foot for 130 kilometres, we were able to engage with a range of communities and ecosystems and better grasp both the problems and opportunities in the region. The mode of walking was essential to our methodology, as it allowed us to stop, listen and absorb all the details that make rural life what it is. We explored places, peoples, textures, smells and landscapes relatively unknown to us and our urban existence, and reflected on ways in which booming urban centres are dependent on rural areas that provide them with everything from food to sand. The riverwalk provided the foundation for our subsequent research and analysis on water governance in Bundelkhand.